Analisis Pembangunan Moda Raya Terpadu terhadap Struktur Perekonomian Provinsi DKI Jakarta Tahun 2013-2019 - Gita Kurnia Selina; R. Mulyo Hendarto (Universitas Diponegoro, 2021)
The Provincial Government of DKI Jakarta Investment on Moda Raya Terpadu (MRT) project is an effort to improve the mass transportation system and overcome congestion problems. The development of Moda Raya Terpadu project will affect the construction sector and other sectors. This study aims to analyze the role of the construction sector, inter-sectoral linkages, degree of sensitivity and spread, multiplier effect, and also analyze the economic impact of government investment on The Moda Raya Terpadu project, in terms of output, income, and job opportunities. This research has been conducted with an input-output analysis. This analysis uses data from the DKI Jakarta Province Input-Output Tables based on producer prices year 2012, classified as 72 sectors that have been aggregated into 17 main sectors.This study indicates that the construction sector has a massive contribution to the formation of output in DKI Jakarta Province. The construction sector has a greater backward linkages value than the forward linkages value. The construction sector has a higher degree of spread therefore this sector can encourage the growth of its upstream sector. The construction sector has owned the largest output multiplier value compare to income multiplier and job opportunities. The Moda Raya Terpadu (MRT) project can create an overall economic output of 42,8 trillion rupiahs, an enlarge in household income of 5,2 trillion rupiahs, and expand for 51 thousand job opportunities